Reforms towards intellectual property-based economic development in Malaysia - Lim, Heng Gee; Abdul Ghani Azmi, Ida Madieha (Wiley-Blackwell, 2009)
It has been constantly asserted that the intellectual property (IP) system is an effective way to enhance creativity, technological innovations, trade and competitiveness. Others, however, maintain that the IP system may not necessarily be the most effective and appropriate way to fuel the economy. This article investigates the role that IP plays in the economic development of Malaysia from 1986 to 2006. In particular, the article examines the impact of IP-based reforms, which includes not only the IP laws but other IP-related policies with a view to determine how these policies contribute to economic development in Malaysia. For this purpose, the article starts with a brief summary of important IP-related policies. Then the article proceeds with an analysis of trends in IP applications such as patent, trademark and industrial design application. Using data such as numbers of IP filing and grant, this article suggests ways in which the reforms in IP-related policies could have supported growth or could have directly influenced trends in IP application in Malaysia. The article further examines the growth of IP applications in four industrial sectors in Malaysia, i.e. automobiles, information technology, pharmaceuticals, and information and communications technology.